Agricultural development model of Jeponan Hamlet, Manggung Village, Ngemplak Sub-district, Boyolali Regency - Wangi, Cyntia Mundi; Putri, Dyah Sancaya; Ardiansyah, M. Rif’an; Salsabila, Talitha Yumna; Indriani, Widya; Antriyandarti, Ernoiz (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Manggung Village has great potential in the agricultural sector, which has long been the mainstay of the village economy. However, the village also faces significant challenges, including high fertiliser prices and irrigation problems that hamper agricultural productivity. This research aims to explore the potential, challenges and impacts of structural, institutional and technological transformation in Manggung Village, and determine the most appropriate agricultural development model. Methods: This research used a qualitative method with data collection techniques in the form of interviews, observation, and note-taking. Primary data was collected through interviews with farmers and community leaders, while secondary data was obtained from literature and other sources of information. Data was analysed to identify the main problems and changes in the village. Findings: The main findings of this research show that Manggung Village is undergoing significant changes in economic and institutional structures, including the application of new technologies such as tractors and rice dryers. While these technologies help to increase efficiency, this transformation has also led to a shift in labour from the agricultural sector to the industrial sector, resulting in a reduction of labour in agriculture. Conclusion: The conclusion of this research shows that a conservation-based agricultural development model is the most suitable for Manggung Village, given the potential for fertile agricultural land and the linkages between the agricultural and livestock sectors. This model is expected to support sustainable development by maintaining environmental quality while improving the economic welfare of the village community. Novelty/Originality of this study: This research makes a novel contribution by highlighting how structural and technological transformations can affect the dynamics of agricultural villages such as Manggung Village. By proposing a conservation-based development model, this research offers a suitable approach to address local challenges while maximising the potential of existing natural resources.